Uncertainties in flexural strength of carbon/glass fibre reinforced hybrid epoxy composites - Dong, Jonathan (Elsevier, 2016)
A study on the flexural behaviours of the of glass and carbon fibre reinforced epoxy hybrid composites is presented in this paper. Two types of glass fibres: S-2 and E, and two types of carbon fibres: T700S and P-100 are investigated. The flexural strength is obtained using an approach based on finite element analysis. Three compressive strength models: Lo-Chim, Budiansky and the shear models are used to obtain the flexural strengths. It is shown from the results that when shear failure occurs, the flexural strength is 20-30% lower compared to other failure modes.